The Hungarian Constitutional Court’s Judgment Concerning the Preliminary Ruling Procedure – Comments on a Rejection Order - Naszladi, Georgina (Pécs journal of international and European law, 2015)
The Hungarian Constitutional Court rejected the admission of a constitutional complaint which held that the violation of the right to fair procedure and right to a fair trial is infringed in case courts refuse their obligation to initiate a preliminary ruling procedure. In the case at hand, the examined questions are constitutional law issues of fundamental importance, and the Hungarian Constitutional Court had the possibility to declare that the Fundamental Law of Hungary does not allow the arbitrary application of law, and that the CJEU may be considered the forum of fair trial.